The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

The Thirtieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2011)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

2016-17 Annual Report - The English Speaking Catholic Council (ESCC) (2017)

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

Annual Report 2018-19 - The English Speaking Catholic Council (ESCC) (2019)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.

Directives on Daycares - The English Speaking Catholic Council (ESCC) (2011)

Statement Regarding the Situation of the Catholic Times - The English Speaking Catholic Council (ESCC) (2010)

Statement on Bill 40 : An Act to Amend the Education Act Principally with Respect to School Organization and Governance - The English Speaking Catholic Council (ESCC) (2019)

General Consultation and Public Hearings on Bill 60 - The English Speaking Catholic Council (ESCC) (2013)
The English Speaking Catholic Council (ESCC) objects to the proposed “Charter,” Bill 60, on the following grounds: • It threatens to erode the historically and legislatively foundational freedoms of conscience, religion, opinion and expression. These are considered to be “first” freedoms in our society and any trend to dilute or undermine these freedoms must be resisted. • It proposes a secularized society in which religious expression and practice are marginalized. It seeks to reframe the public discussion so that the exercising of Charter-protected rights is to be understood as an imposition upon society which requires the permission of the State. • It muddies the separation of Church and State as it proposes the State has the power to define the nature of religious belief, practice and expression. • In all of the aforementioned points the role of the State is elevated above the proper parameters of a democratically elected and responsible government. The ESCC calls upon the Government of Quebec to withdraw Bill 60.

Consultation générale et auditions publiques sur le projet de loi n° 60 - The English Speaking Catholic Council (ESCC) (2013)
Le Conseil catholique d'expression anglaise (CCEA) s’oppose à la charte proposée par le projet de loi 60, et ce, pour les raisons suivantes : • Il menace d’éroder, d’un point de vue historique et juridique, les libertés fondamentales de conscience, de religion, d’opinion et d’expression. Il s’agit des libertés « primordiales » dans notre société et il faut s’opposer à tout ce qui tend à diluer ou à réduire ces libertés. • Il propose une société sécularisée dans laquelle l’expression et la pratique religieuses sont marginalisées. Il cherche à recadrer le débat public de manière à ce que l’exercice des droits et libertés protégés par les chartes soit perçu comme imposé à la société et nécessitant la permission de l’État. • Il formule une notion embrouillée de la séparation de l’Église et de l’État en proposant que l’État a le pouvoir de définir la nature des croyances, de la pratique et de l’expression religieuses. • Dans tous les points susmentionnés, il situe le rôle de l’État au-dessus des paramètres de gouvernance appropriés d’un gouvernement élu démocratiquement et responsable. Le CCEA demande au gouvernement du Québec de retirer le projet de loi 60.